The chinese diaspora: presente and future in Portugal - Pestana, Luís (2018)
The Chinese people have always been characterized by great mobility. In the nineteenth century many were those who sought their fortune outside Imperial China. In the Portuguese case, the process was slower since Portugal was traditionally seen as a crossing point for other stops rather than a final destination. However, this trend began to change from the 1970s onwards. Nowadays, reality shows that this community is changing again, because of the transformations of its own country. As such, more and more students and investors who are holders of the Visa Gold, see in Portugal the way to improve their academic careers and an entry into the European Union.